Influence of environment conditioning on the interlaminar fracture toughness of a graphite/epoxy unidirectional material. (15th November 2018) - Boni, L.; Fanteria, D.; Lazzeri, L.; Panettieri, E.; Mariani, U.; Rigamonti, M.
Abstract: An experimental program has been carried out at the Department of Civil and Industrial Engineering of the University of Pisa, in collaboration with Leonardo Helicopter Division (formerly AgustaWestland), for the evaluation of the interlaminar fracture resistance of Hexcel 913C-HTA, a graphite/epoxy system commonly used in many aeronautical platforms. The study comprised mode I tests (carried out on DCB specimens), mode II tests (using ENF specimens) and Mixed Mode I + II tests (carried out by means of the Mixed Mode Bending procedure). A complete description of the fracture toughness was so obtained, at Room Temperature and on dry specimens. This picture was completed by the assessment of temperature and moisture effects, by means of a few additional tests, performed at high temperature, 70 °C, on DCB and ENF saturated coupons, conditioned in an environmental chamber at 70 °C and 85% RH. The results showed an increase in mode I resistance and a decrease in mode II toughness, in agreement with similar results available in the literature.